Pengaruh Tepung Tanaman Meniran (Phyllanthus niruri Linn) Sebagai Pakan Tambahan Terhadap Mikroflora Usus Halus Ayam Pedaging - Lestariningsih Lestariningsih; Osfar Sjofjan; Edhy Sudjarwo (Jurnal Agripet, 2015)
(Effect of meniran powder as feed additive on microflora small intestine of broiler)ABSTRACT. Meniran plant powder has potential as feed additive that can help balancing the microflora of small intestine of broilers . However, it is but not yet known that the best optimum level of meniran plant powder given effect on small intestine microflora of broiler. The purpose of this study was to find the best level of meniran powder that used to inhibited the growth of small intestine microfora (lactad acid bacteria and Eschirichia coli). This study consist of 4 treatments which were (P0= Antibiotic 100 %, P1= meniran powder 0 %, P2= meniran powder 0,8 % and P3 = meniran powder 1,2 %). Variable tested in this study wereLAB and Eschirichia coli. Nested Completely Randomized Design method used and if there was a different effect , it would tested by Duncans Multiple Range Test. The result of the research indicated that meniran plant powder had a not significant effect (P0.05) on small intestine microflora of broiler (BAL dan Escherichia coli). It was noted that supplementation meniran plant powder at level of 0,8% gave the best effect on the small intestine microflora.